Disentangling gender‐differentiated impacts on food security and poverty: Empirical evidence from Vietnam. (23rd December 2021) - Bairagi, Subir; Mishra, Ashok K.; Tran, Dat Q.
Abstract: This study examines the association between a household head's gender and food insecurity and poverty in Vietnam using data from the Vietnam Household Living Standard Survey and exogenous switching treatment effect regression. The findings suggest that food insecurity and poverty differ by the gender of the household head and by the presence (de facto) or absence (de jure) of a spouse among female‐headed households (FHHs). On average, FHHs are less food secure and live in more poverty than male‐headed households (MHHs). Still, their status would improve if they had the same returns on their observed characteristics as those estimated for MHHs. The results further reveal that the probabilities of food insecurity and poverty would be lower if de jure FHHs had the same returns on their observed characteristics as those estimated for MHHs. The probability of poverty would also be lower if de jure FHHs had the same returns on their observed characteristics as those estimated for de facto FHHs. The likelihood of poverty and food insecurity would remain similar if de facto FHHs had the same returns on their observed characteristics as the ones estimated for MHHs. Among all groups, de jure FHHs are likely to be the most vulnerable in Vietnam, suggesting gender equality policies are required. Finally, higher education, increased nonfarm incomes and greater land‐use rights can substantially enhance Vietnam's food security and poverty levels.